Chemical Oxygen Demand (COD) Analysis Ink Printing Waste Water Using Titrimetry Method: Analisis Chemical Oxygen Demand (COD) Air Limbah Tinta Industri Percetakan Menggunakan Metode Titrimetri - Dian Khristiani Suhari; Peni Pujiastuti (Jurnal Kimia dan Rekayasa, 2020)
The printing industry produces wastewater from the ink used. Contains organic and inorganic pollutants such as lead, cadmium, chromium and zinc. Having a quality that exceeds the quality standards for wastewater. If it is discharged into the environment it can pollute the receiving water body. Need to do an analysis of organic pollutant content, by measuring the parameters of Chemical Oxygen Demand (COD). Determination of COD numbers in printing industry wastewater ink using titrimetry method (SNI 6989.73: 2009). Perform oxidation-reduction titration using Ferro Ammonium Sulfate (FAS) solution in printing industry ink wastewater. This study conducted three sampling replications. The results of the first day research obtained a COD rate of 33,088 mg /L; second day 69,694.6 mg /L; third day 67,830.4 mg /L. All three samples had COD figures exceeding the printing industry wastewater quality standard of 125 mg / L. Printing industry wastewater is not suitable to be discharged into the environment. Abstrak Industri percetakan menghasilkan limbah cair dari tinta yang digunakan. Mengandung polutan organik dan anorganik seperti timbal, kadmium, kromium, dan zink. Memiliki kualitas yang melebihi baku mutu air limbah. Apabila dibuang ke lingkungan dapat mencemari badan air penerima. Perlu dilakukan analisis kandungan polutan organik, dengan mengukur parameter Chemical Oxygen Demand (COD). Penentuan angka COD pada air limbah tinta industri percetakan dengan menggunakan metode titrimetri (SNI 6989.73:2009). Melakukan titrasi oksidasi-reduksi menggunakan larutan Ferro Amonium Sulfat (FAS) pada sampel air limbah tinta industri percetakan. Penelitian ini melakukan tiga kali ulangan sampling. Hasil penelitian hari pertama diperoleh angka COD sebesar 33.088 mg/L; hari kedua sebesar 69.484,6 mg/L; hari ketiga sebesar 67.830,4 mg/L. Ketiga sampel memilik angka COD melebihi baku mutu air limbah industri percetakan sebesar 125 mg/L. Air limbah tinta industri percetakan tidak layak dibuang ke lingkungan.